Design expositivo: modernismo italiano revisitado no museu de arte de São Paulo "Assis Chateaubriand" - BARBOSA, Caroline Carvalho (2017)
The return of exhibitions at the São Paulo Art Museum “Assis Chateaubriand” - MASP from the year 2015 is a review of the museological program with ways to outline the next Maspian actions. The Italian exhibition design, delineated from the influence of El Lissitisky and the production within the European vanguards, had in Brazil MASP as a space for its expression through mainly the performance of Lina Bo Bardi. From this context, the present research aims to highlight aspects of Italian exhibition design, influenced by the premises of modern Italian architecture and art. The exhibition Fashionable art: collection MASP Rhodia (2015-2016) presents 79 pieces of clothing that were donated by Rhodia to the MASP collection in the year 1972, and this exhibition, through the analysis of its exhibition devices, the object of this research. Here we made use of the bibliographical and documentary techniques, if the latter stopped the analysis of documents, texts, drawings and images related to the exhibition Fashionable art: MASP Rhodia collection, held at the MASP Documentation Center. The exhibition presents a different display from those that marked the Italian production in the field of exhibition design.